Icons as Maps: Cartographic Icons in Orthodox Art - Todorova, Rostislava (Eikón / Imago, 2015)
Although a comparison between Orthodox icons and geographic maps sounds like an extravagant idea, if we set them in a broader context, we will see that they are actually akin. Both, the Orthodox εικών and the medieval mappamundi are symbolic images that represent cosmological concepts, showing the essence and character of the Universe in images. They enable people to overcome their natural limitations and see what is invisible to their eyes.